Can Managers Use Accruals Quality for Creating Investment Opportunity Set and Increasing Firm Value? - Bayu Adi Nugroho; Jasman Jasman (Binus Business Review, 2018)
There were two main objectives of this research. Firstly, the researchers analyzed the impact of accruals quality and debt on firm value. Secondly, the researchers studied whether managers of a highly leveraged firm could use discretionary accruals for Investment Opportunity Set (IOS). The sample consisted of Indonesian manufacturing firms listed from 2013 to 2016. The researchers utilized Generalized Method of Moments (GMM) method and purposive sampling. The researchers find that accruals quality positively affects firm value. The results also suggestthat there are differences in accruals quality between highly leveraged and unleveraged firms. Furthermore, the results indicate that the more intensive the exploitation of accruals quality is, the greater the positive impact of such activity on firm value will be. Additionally, high-accrual leveraged firms borrow more debt than low-accrual unleveraged firms. Then, unleveraged firms have better accruals quality and cash flow, and highly leveraged firms have more significant accounts receivable and slightly better value of IOS. The findings suggest that managers of highly leveraged firms can use discretionary accruals to increase the value of IOS.